Личностные особенности больных шизофренией с депрессивной и парадепрессивной симптоматикой в структуре заболевания = Personality features of schizophrenia patients with depressive and predepression symptoms in the structure of the disease - K. A. Sincha (Kazimierz Wielki University, 2016)
Sincha K. A. Личностные особенности больных шизофренией с депрессивной и парадепрессивной симптоматикой в структуре заболевания = Personality features of schizophrenia patients with depressive and predepression symptoms in the structure of the disease. Journal of Education, Health and Sport. 2016;6(4):21-30. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49386 http://ojs.ukw.edu.pl/index.php/johs/article/view/3443     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 05.04.2016.     Личностные особенности больных шизофренией с депрессивной и парадепрессивной симптоматикой в структуре заболевания   К. А. Синча   Запорожский государственный медицинский университет МЗ Украины, Запорожье, Украина   Реферат Последние десятилетия рядом исследователей отмечено наличие депрессивных включений в структуре шизофрении. Однако, несмотря на значимую роль депрессивной симптоматики у больных шизофренией, до сих пор не установлены особенности ее структуры, этио- и психопатогенеза, которые бы позволили улучшить качество диагностики и терапии. Цель исследования - установить особенности состояний и свойств личности больных шизофренией с депрессивной и парадепрессивной симптоматикой в структуре заболевания. На базе КУ «Областная клиническая психиатрическая больница» ЗОС было обследовано 137 больных, которые проходили стационарное лечение. Основную группу (ОГ) составили 107 больных шизофренией (F20). Среди них - 55 женщин и 52 мужчины. Средний возраст в группе составил 46,33±1,36 лет. Группу сравнения (ГС) составили 30 больных шизоаффективным расстройством, смешанный тип (F25). Среди них - 18 женщин и 12 человек. Средний возраст в группе составил 48,93±2,47 год. Методы исследования: анамнестический, катамнестический, клинико-психопатологический, психодиагностический. В результате исследования были установлены особенности депрессивной симптоматики у больных шизофренией. Отмечена диссоциация между выявляемостью депрессивных феноменов по данным клинико-психопатологического и психодиагностического исследований, что может свидетельствовать о явлениях гипо- и гипердиагностики, обусловленных как несовершенством диагностического инструментария, так и присущей шизофрении амбивалентности психических процессов. По данным клинико-психодиагностического исследования у ⅓ больных шизофренией диагностировалась симптоматика депрессивного и парадепрессивного круга, доходящая до уровня клинически выраженной депрессии и требующая специфической коррекции. Изучение личностных особенностей больных шизофренией позволили установить различия в генезе депрессивной симптоматики, диагностируемой у пациентов, в полной мере нашедшие отражение в трех вариантах профилей личности больных шизофренией с депрессивными явлениями в структуре заболевания: анозодепрессивный (парадепрессивный), параноидно-невротический (параноидно-дисфорический), социогенно-невротический (ятрогенно-невротический).   Ключевые слова: депрессия, шизофрения, психопатогенез, психодиагностика.     PERSONALITY FEATURES OF SCHIZOPHRENIA PATIENTS WITH DEPRESSIVE AND PREDEPRESSION SYMPTOMS IN THE STRUCTURE OF THE DISEASE   K. A. Sincha   Zaporizhzhia State medical University Ministry of Health Care of Ukraine   Summary Last decades several researchers noted the presence of depressive inclusions in the structure of schizophrenia. However, despite the significant role of depressive symptoms in patients with schizophrenia, still the peculiarities of its structure, the ethio - and psychopathogenesis, which would allow to improve the quality of diagnosis and therapy. The purpose of the study is to establish the specific conditions and personality traits of patients with schizophrenia with depressive and paradepressive symptoms in the structure of the disease. On the basis of Public Health Institution «Regional clinical mental hospital» of the Zaporizhzhian regional council  examined 137 patients who underwent hospital treatment. Research group were 107 patients with schizophrenia (F20). Among them - 55 women and 52 men. The average age in the group was 46,33 ± 1,36 year  old. Comparison group consisted of 30 patients with schizoaffective disorder, mixed type (F25). Among them - 18 women and 12 men. The average age in the group was 48,93 ± 2,47 y. o. Research methods: anamnestic, catamnestic, clinico-psychopathological, psychodiagnostic methods. In the result of the study the features of depressive symptoms in patients with schizophrenia. Marked dissociation between the detection rate of depressive phenomena according to clinical psychopathological and psychodiagnostic research that may indicate the phenomena of hypo - and overdiagnosis, due to the imperfection of diagnostic tools and the inherent ambivalence of schizophrenia mental processes.